Preliminary estimate of contribution of Arctic nitrogen fixation to the global nitrogen budget - Sipler, Rachel E.; Gong, Donglai; Baer, SE; Sanderson, MP; Roberts, QN; Mulholland, M; Bronk, DA (Limnology and Oceanography Letters, 2017)
Dinitrogen (N-2) fixation is the source of all biologically available nitrogen on earth, and its presence or absence impacts net primary production and global biogeochemical cycles. Here, we report rates of 3.5-17.2 nmol N L-1 d(-1) in the ice-free coastal Alaskan Arctic to show that N-2 fixation in the Arctic Ocean may be an important source of nitrogen to a seasonally nitrogen-limited system. If widespread in surface waters over ice-free shelves throughout the Arctic, N-2 fixation could contribute up to 3.5 Tg N yr(-1) to the Arctic nitrogen budget. At these rates, N-2 fixation occurring in ice-free summer waters would offset up to 27.1% of the Arctic denitrification deficit and contribute an additional 2.7% to N-2 fixation globally, making it an important consideration in the current debate of whether nitrogen in the global ocean is in steady state. Additional investigations of high-latitude marine diazotrophic physiology are required to refine these N-2 fixation estimates.